Successful Management of Ischemic Stroke : A Case Report and Literature Review - Gunardi, Monicha Vanessa Rahman; Mariska; Nabila, Siti Naila (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2024)
Introduction: Stroke is a clinical condition characterized by the sudden onset of focal (or global, in cases of coma) neurological symptoms that persist for over 24 hours or result in death, with no clear cause other than a vascular issue. Case Description: Male, 62 years old, with chief of complaint of mouth dropped to the right since 1 day before admission. Complaints made the patient speak more difficult, slow and unable to form sentences. Physical examination show parese CN. VII UMN dextra. Siriraj score -5 and Head NCCT show cerebral infarction in the internal capsula interna. Patient was diagnosed with ischemic stroke. Discussion: The use of a scoring system can be useful when there are no brain imaging facilities that can clearly distinguish the causative pathology of stroke. criteria for diagnosis of ischemic stroke are symptoms of global neurological deficits or one / several focal neurological deficits that occur suddenly with evidence of brain imaging images (CT scan or MRI). The most common differential diagnosis is hemorrhagic stroke. Conclusion. Early recognition and appropriate treatment is important to cure acute ischemic stroke to achieve good quality of life and prevent further infarct to brain tissue. Keyword: Craniotomy, Brain Metastases, Hepatocellular Carcinoma